A method to increase the survival of probiotic bacteria Lactobacillus brevis at a lowered pH - Jurkowski, Andrzej; Kozioł, Jacek J.; Gronczewska, Ewelina (Biological Letters, 2019)
Lactobacillus brevis PCM 2570 is a strain of lactic acid bacteria, i.e. probiotic bacteria whose major fermentation product is lactic acid. The efficiency of lactic acid production is limited by the value of ambient pH. This study aimed to increase the survival of this bacterial strain at a reduced pH (3.9), which would result in an increased yield of lactic acid fermentation. In our experiment the survival rate of probiotic bacteria L. brevis PCM 2570 was increased 1.2-fold to 6.96-fold due to the presence of Fe3O4 magnetic nanoparticles, as compared to the control. The minimum concentration of nanoparticles with a positive effect was 8 mg/ml, but the optimum concentration was 20 mg/ml.